2015
DOI: 10.1590/s1677-5538.ibju.2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ureteroscopic Management of Horseshoe Kidney Renal Calculi

Abstract: Purpose:To evaluate the clinical efficacy of flexible ureteroscope (F-URS) combined with holmium laser lithotripter in treating renal calculi in horseshoe kidney.Materials and Methods:From November 2010 to December 2013, the medical history and charts of sixteen patients (mean age 42.9±11.6 years, range 26-66 years), including 13 males and 3 females were analyzed retrospectively. Mean stone burden was 29±8 mm (range 17-42 mm2). Mean stone digitized surface area (DSA) was 321±94 mm2 (range 180-538 mm2). Under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…Impaired drainage of the collecting system and associating ureteropelvic obstruction predispose the patient to urinary tract infection and urolithiasis 4 . In our case, the patient had undergone nephrolithotomy once on the right side of horseshoe kidney, but no residual renal calculi were found.…”
Section: Discussionmentioning
confidence: 65%
“…Impaired drainage of the collecting system and associating ureteropelvic obstruction predispose the patient to urinary tract infection and urolithiasis 4 . In our case, the patient had undergone nephrolithotomy once on the right side of horseshoe kidney, but no residual renal calculi were found.…”
Section: Discussionmentioning
confidence: 65%
“…The mean operative time was 61.3 min (range 14-185 min). While six studies report a post-operative stent placement in all of their patients [13,14,19,21,22,26], in the remaining studies this varied from 46.2 to 84% and was at the surgeon's discretion [15][16][17][23][24][25]. The mean hospital stay across studies was 1.7 days (range 0.5-9 days) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Ding et al [19] Post-operative pyrexia n = 3 None Blackburn et al [20] Complications not reported Complications not reported Gokce et al [21] Haematuria n = 3 Post-operative pyrexia n = 1…”
Section: Nonementioning
confidence: 99%
See 1 more Smart Citation
“…Horse shoe kidney occurs in 0.25% of the population, or about 1 in 400 persons (1). Previously, up to one-third of individuals with horseshoe kidney had hydronephrosis secondary to UPJ obstruction (8). In the modern era, horseshoe kidneys are frequently discovered incidentally, and their apparent hydronephrosis often shows a non-obstructed pattern on radionuclide scanning (9).…”
Section: Discussionmentioning
confidence: 99%